HURUF MA’ANI DAN MASALAH DALALAH (Penelitian Pendidikan tentang Kalimah sifat Ketuhanan Pembuktian dengan Pancaindra) - Ratno, Dedi (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2024)
If a letter indicates the meaning of another sentence, it is called a maani letter, and this rule is what has been formulated by nahwu scholars. The study of maani letters has a strong connection to understanding the meaning and basic legal basis of the Quranic text by means of ijtihad or ta'wil. This is because many legal arguments and fiqh issues depend on the meaning of the text through the wasilah dalalah (simantics) determined by the letters of the text. Not only limited to the study of tafsir and lughoh, ma'ani letters that have various dalalah also contribute significantly to the development of other sciences such as Ushul fiqh, aqidah, fiqh, and sharia science or Islamic law in general. This has led to endless debates between the schools of fiqh and aqidah. Seeing the importance of this study, the urgency of studying the science of dalalah and all that is related to lughoh is a prevalence. To understand the intent and purpose of sharia law from the Arabic texts of the Quran, Sunnah and the ijtihad of previous scholars.